Gastrointestinal bleeding - Gralnek, I. M. (Endoscopy, 2012)
There were a number of interesting abstracts presented at the 2012 Digestive Disease Week (DDW; 19 – 22 May, San Diego, California, USA) that covered gastrointestinal bleeding and endoscopy. The following abstracts are those that were found to have particular high clinical importance and the potential for direct impact on the endoscopic care of patients.